High-fat diet-induced obesity affects sulfurtransferases activity in mice hearts - Szlęzak, Dominika; Misterka-Kozaka, Anna; Majewska-Szczepanik, Monika; Bronowicka-Adamska, Patrycja (Folia Medica Cracoviensia, 2026)
Introduction: Obesity is a chronic disease with complex etiology, characterized by excessive accumulation of fat tissue, which poses a health hazard and increases, among others, risk of cardiovascular diseases. Hydrogen sulfide (H2S), an endogenous gaseous transmitter, plays an important role in the cardiovascular system, affecting blood pressure and heart function. Aim: The aim of this study was to determine the effect of high-fat diet-induced (HFD-induced) obesity to hydrogen sulfide metabolism in mice hearts. Materials and Methods: The research material consisted of hearts collected from male wild-type C57BL/6 mice fed for 8 weeks with a normal diet (ND) or high-fat diet. Ex vivo analyses included testing the activity of selected sulfur enzymes (cystathionine gamma-lyase — CGL, 3-mercaptopyruvate sulfurtransferase — MPST, and thiosulfate sulfurtransferase — TST), determining the sulfane sulfur level, and examining the ability of tissues to produce hydrogen sulfide. Results: Tissues collected from HFD-fed mice were characterized by a lack of CGL activity, increased TST activity, and higher levels of sulfane sulfur compared to group of ND mice. Additionally, the capacity to produce H2S was higher in the hearts of HFD mice. Conclusions: Our study shows that HFD-induced obesity affects hydrogen sulfide levels and sulfur enzyme activity in mice hearts. It can be speculated that the increased ability of HFD mice tissues to produce H2S is a compensatory mechanism for obesity-induced changes. The conducted research indicates the key importance of sulfurtransferases, MPST and TST, in sulfur metabolism in the heart and indicates a new area for further analysis.